Bridging Real and Virtual: A Spiritual Challenge Journal for Religion, Film and Media - Michael R. Heim (Journal for Religion, Film and Media, 2017)
The question of how to bridge virtuality and reality intensified in 2016 with the release of several consumer products. The article begins by reviewing two anxieties about virtual reality raised at a 1999 conference. To address these anxieties, the paper draws on post-Jungian archetypal psychology (James Hillman, Thomas Moore) and the retrieval of Renaissance theology (Marsilio Ficino). Two experiences with Samsung Gear VR then illustrate how classic archetypal elements can contribute to active procedures for bridging the virtual and the real.